PENGARUH CONTENT MARKETING DAN ONLINE CONVENIENCE TERHADAP NIAT BELI PRODUK KOSMETIK DI APLIKASI TIKTOK SHOP - Vivi Pratiwi Wulandari; Kristina Anindita Hayuningtias (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the influence of content marketing and online convenience on consumer purchase intent on cosmetic products on TikTok Shop. The increasing use of TikTok as an online shopping platform, especially among the younger generation, encourages cosmetics business people to use efficient digital marketing strategies. Attractive and informative content marketing and convenience in online shopping are two key factors that are suspected to affect consumer purchase intention. This study uses a quantitative approach with a purposive sampling method. Data were collected through questionnaires distributed to 170 respondents who had the desire to buy cosmetic products at TikTok Shop and analyzed using SPSS by conducting validity tests, reliability tests, multipe linear regression analysis, model tests (determination coefficient, F-test, t-test) to determine the influence of content marketing and online convenience on the intention to buy cosmetic products at TikTok Shop. The results of this study indicate that content marketing has a positive and significant influence on consumer purchase intentions, online convenience has a positive and significant effect on consumer purchase intentions. simultaneously content marketing and online convenience together have a simultaneous effect on consumer purchase intentions.